Aplicação de zinco em sementes de sorgo cv. BRS 304: efeitos na nutrição e no crescimento inicial - Prado, Renato de Mello [UNESP]; Romualdo, Liliane Maria; Rozane, Danilo Eduardo [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The effect of zinc applied in seeds oil the nutrition of sorghum is affected by the sources and applied rate. The present work aimed to evaluate zinc application, front two sources, on the nutrition and initial growth of a culture of sorghum cv. BRS 304, cultivated in sand. The treatments consisted of five rites (0, 14.3, 28.6, 57.2 and 114.4 g kg(-1) of seed) and two zinc sources - sulphate (22% Zn) and oxide (50% Zn). At 25 days after sowing, the plants were cut. The aerial and root dry mass was evaluated, and the levels and accumulation of Zn in the plants were determined. The of seeds, in oxide form, provided adequate initial growth of application or 14 g Zn kg(-1) sorglitim cv. BRS 304. The sulphate source promoted greater absorption of Zn for the plants, reaching in its highest dosis, high levels of the nutrient in the aerial part (> 4170 mg kg(-1)) and developing characteristic symptoms of phytoxicity.
Zinc application in seeds of sorghum cv. BRS 304: effects on nutrition and initial growth
Keywords: Sorghum bicolor; micronutrient; fertilization; absorption